ANTIMICROBIAL RESISTANCE IN BACTERIA ISOLATED FROM TROPICAL COASTAL WATERS OF PENINSULAR MALAYSIA - Kian, Giap You; Chui, Wei Bong; Choon, Weng Lee (Malaysian Journal of Science, 2012)
Thirty three heterotrophic bacteria isolated from tropical coastal waters in Peninsular Malaysia were tested for susceptibility to 15 different antibiotics representing nine different classes of antimicrobial agents. We found that tetracycline, sulfonamide, mecillinam, sulfamethoxazole, erythromycin, and streptomycin resistance were predominant among the bacterial isolates. Resistance to chloramphenicol, ampicillin, vancomycin, norfloxacin, ofloxacin and trimethoprim/sulfamethoxazole were less common. All of the bacterial strains were susceptible to meropenem, imipenem, and ciprofloxacin. Approximately 70% of the isolates were resistant to two or more structural classes of antibiotic. Findings from this preliminary study indicated the prevalence of antibiotic resistance bacteria in the coastal waters of Penisular Malaysia. ABSTRAK Kerentanan tiga puluh tiga bakteria heterotrofik yang diasingkan dari perairan pantai tropika di Semenanjung Malaysia telah diuji terhadap 15 antibiotik yang mewakili sembilan kelas agen antimikrobial. Kami mendapati bahawa ketahanan terhadap tetracycline, sulphonamide, mecillinam, sulfamethoxazole, erythromycin dan streptomycin adalah predominan di antara bakteria isolat. Resisten terhadap chloramphenicol, ampicillin, vancomycin, norfloxacin, ofloxacin dan trimethoprim/sulfamethoxazole adalah kurang lazim. Semua strain adalah peka terhadap meropenem, imipenem dan ciprofloxacin. Sekitar 70% daripada bakteria strain adalah resisten terhadap dua atau lebih struktural kelas antibiotik struktural. Penemuan kajian preliminari ini menunjukkan kelaziman resistensi bakteria di perairan pantai Semenanjung Malaysia terhadap antibiotik. (Keywords: marine bacteria, antibiotic, multidrug resistance, coastal waters)